Kontestasi Ruang: Peruntukan Ruang di Bumi Perkemahan Sekipan - Hudzaifah Al Fathin; Nurhadi Nurhadi; Danang Purawanto (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Space contestation in the tourism sector is encouraged because of the multiplier effect that can increase community empowerment, with implications for the potential for confusion and struggle for space management rights that are detrimental to the community. The research aims to identify the occurrence of space contestation and community rights to the space. The research uses a case study approach with qualitative methods located at the Sekipan campground and uses the theory production of space to analyze the problem. As a result, there has been space contestation in the area involving actors from the community, government and private companies. The community's rights in the area are hampered by the management that is administratively owned by Perhutani, but the community remains socio-historically bound to the production of the area's initial space.